A mathematical model for calculating the saturator of the sugar production - Ovcharuk, Vladimir; Yushchuk, Inna; Metlov, Sergei (My University, 2013)
Work on optimization of calculation process for the equipment intended for the absorption of carbon dioxide with the aim to neutralize calcium hydroxide when purifying crude juice in sugar production. Developed a mathematical model and parametric scheme to calculate the process of carbonation. Determined that the saturation with carbon dioxide of kiln gas negative impact on coefficient of its use. Was established that with the increase of CO2 in the gas efficiency of its use decreases.
Keywords: purifying crude juice; sugar production; optimization of calculation; очистка дифузійного соку; оптимізація розрахунку; цукрове виробництво; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки